Problems of a written survey of interested persons as witnesses in the civil process of Ukraine - Sapeiko, L. V.; Сапейко, Л. В.; ORCID: http://orcid.org/0000-0001-6911-8283 (Visegrad journal on human rights. – 2019. – № 6 (Vol. 3). – P. 166-170, 2019)
Розглянуто процедуру письмового опитування учасників справи як свідків. Виявлено проблеми такої процедури та запропоновано шляхи реформування цивільного процесуального законодавства України щодо окресленого правового питання.

The article discusses the procedure for a written survey of the case participants as witnesses, reveals the problems of such a procedure and suggests ways of reforming the civil procedural legislation of Ukraine regarding the designated legal issue.

Рассмотрена процедура письменного опроса участников дела как свидетелей. Выявлены проблемы такой процедуры и предложены пути реформирования гражданского процессуального законодательства Украины по определенному правовому вопросу.
Проблематика письмового опитування заінтересованих осіб як свідків у цивільному процесі України
Sapeiko, L. Problems of a written survey of interested persons as witnesses in the civil process of Ukraine / Liudmyla Sapeiko // Visegrad journal on human rights. – 2019. – № 6 (Vol. 3). – P. 166-170.
Keywords: Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; письмове опитування; written survey; письменный опрос; свідки; witnesses; свидетели; заінтересовані особи; interested persons; заинтересованные лица; заява свідка; witness statement; заявление свидетеля; суд; court; publikatsii u zarubizhnomu vydanni; цивільне судочинство; законодавство; legislation; законодательство